2021
DOI: 10.1097/inf.0000000000003231
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With 30-Day Mortality Among Neonates With A. baumannii Sepsis

Abstract: Background: Acinetobacter baumannii sepsis constitutes an extreme threat with a poor prognosis and is a difficult infection to control, especially in Asia. Moreover, a knowledge gap in the risk of mortality in neonatal A. baumannii sepsis still exists. Methods: This study aimed to identify the risk factors of mortality in neonates with A. baumannii sepsis in Thailand from 1996 to 2019. A multivariable logistic regression model was analyzed for nonsurvivors and survivors of neonatal A. baumannii sepsis. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The disease was reported more in boys in other surveys in Iran and different parts of the world (14). Although gender is considered a risk factor for infections and sepsis during the neonatal period, there is no difference between boys and girls after this period, especially for viral infections (15). About 8%of children were treated twice, and some had more than twice a diagnosis of COVID-19.…”
Section: Discussionmentioning
confidence: 92%
“…The disease was reported more in boys in other surveys in Iran and different parts of the world (14). Although gender is considered a risk factor for infections and sepsis during the neonatal period, there is no difference between boys and girls after this period, especially for viral infections (15). About 8%of children were treated twice, and some had more than twice a diagnosis of COVID-19.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, GNB sepsis ended fatally in 67.7% ( Acinetobacter ), 58.2% ( Klebsiella ), and 58.3% ( Pseudomonas ) of patients, with multiple antibiotic resistance as the only confirmed predictor of fatal outcome [ 37 ]. The main contributors to a fatal outcome in newborns with Acinetobacter sepsis were septic shock, with odds of 41.38, and inadequate antibiotic treatment, showing a 10-times-higher risk [ 38 ]. According to a recent systematic review, antibiotic resistance caused by insufficient empiric care is a serious concern in the rising prevalence of GNB sepsis in infants [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, after analysing the use of antibiotics before a positive blood culture was observed, we found that when there was no significant difference in the TBSA and the third-degree burn are between the two groups of patients, whether the antibiotics that were used were appropriate had no effect on the length of hospital stay, the length of ICU stay, or in-hospital mortality. However, it has previously been reported that whether or not the initial antibiotic used for in patients with infection is appropriate is not associated with mortality 36,37 and that the use of inappropriate initial antibiotics in infected patients leads to an increase in mortality 25,38 www.nature.com/scientificreports/ Such contradictory results may be explained as follows: 1. In addition to the selection of appropriate antibiotics, whether anti-infective treatment is effective is also related to the specific bacterial resistance and the method of antibiotic administration 25 .…”
Section: Discussionmentioning
confidence: 99%